Influencing factors of emotional well-being in Chinese patients with gastroenteric tumours: the role of mindfulness practice, social support and patient-centred communication - Peng, Min; Liu, Shu-Rui; Liu, Shi-Yun; Li, Ruo-Xi; Zhang, Yin-Ping (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to explore the factors influencing the emotional well-being of patients with gastroenteric tumours and to examine the mediating roles of beliefs about cancer and health self-efficacy in mindfulness practice, social support and patient-centred communication (PCC).MethodsA convenience sample of 517 patients with gastroenteric tumours who visited the oncology department of six tertiary hospitals in Lanzhou City, Gansu Province, between 26 July 2022 and 30 September 2022 was selected for this study. General demographic and disease information of the patients was collected, and the relationships among mindfulness practice, social support, PCC, beliefs about cancer, health self-efficacy and emotional well-being were analysed.ResultsMindfulness practice, social support, beliefs about cancer and health self-efficacy had positive effects on emotional well-being (p < 0.05). Beliefs about cancer mediated the relationships between mindfulness practice (effect size, 0.025), social support (effect size, 0.033), and PCC (effect size, 0.079) and emotional well-being. Notably, health self-efficacy also served as a mediator in the relationships between mindfulness practice (effect size, 0.093), social support (effect size, 0.040), PCC (effect size, 0.057) and emotional well-being, with all these mediation effects reaching statistical significance (p < 0.05).ConclusionSocial support, beliefs about cancer, mindfulness practice and health self-efficacy had positive effects on the emotional well-being of patients with gastroenteric tumours. Beliefs about cancer and health self-efficacy mediated the effects of mindfulness practice, social support and PCC on emotional well-being.